Improved flame retardancy by synergy between cyclotetrasiloxane and phosphaphenanthrene/triazine compounds in epoxy thermoset. Issue 12 (25th September 2017) - Qiu, Yong; Wachtendorf, Volker; Klack, Patrick; Qian, Lijun; Liu, Zhen; Schartel, Bernhard
Abstract: A siloxane compound (MVC) and a bi‐group phosphaphenanthrene/triazine compound (TGD) were employed in epoxy thermosets to explore high‐efficiency flame retardant systems. With only 1 wt% MVC and 3 wt% TGD, an epoxy thermoset passed UL 94 V‐0 rating test and achieved a limiting oxygen index value of 34.0%, exhibiting an excellent flame retardant effect. The MVC/TGD system not only decreased the peak value of heat release rate and effective heat of combustion but also imparted an improved charring ability to thermosets, thereby outstandingly reducing the flammability of 1%MVC/3%TGD/EP. Compared with the fire performance of 4%TGD/EP and 4%MVC/EP, the MVC/TGD system showed an obvious flame retardant synergistic effect, mainly depending on the general improvement of flame inhibition, charring and barrier effects of the thermoset during combustion. Evolved gas analysis combined with condensed‐phase pyrolysis product analysis jointly revealed the details of the changed pyrolysis mode. © 2017 Society of Chemical Industry Abstract : The synergistic effect between cyclotetrasiloxane and phosphaphenanthrene/triazine compounds endowed epoxy thermosets with an excellent flame retardant effect with distinctly optimized flame retardant actions in both gas and condensed phases.